2023
DOI: 10.1111/bjh.19049
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐derived exosomes promote the induction of monocytic myeloid‐derived suppressor cells from peripheral blood mononuclear cells by delivering miR‐106a‐5p and miR‐146a‐5p in multiple myeloma

Abstract: SummaryThe shift of the tumour immune microenvironment to a suppressive state promotes not only the development and progression of the disease in multiple myeloma (MM) but also the development of resistance to immunotherapy. We previously demonstrated that myeloma cells can induce monocytic myeloid‐derived suppressor cells (M‐MDSCs) from healthy peripheral blood mononuclear cells (PBMCs) via the concomitant secretion of CC motif chemokine ligand 5 (CCL5) and macrophage migration inhibitory factor (MIF), but an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Experiments have demonstrated that exosomes derived from BMSCs provide a safeguard against bortezomib by activating certain proteins (c-Jun, p38, p53, AKT) and influencing the expression of Bcl-2, caspase 9, caspase 3, and PARP [ 145 ]. In addition, exosomes have the ability to influence the immune response in the BMME, creating a suppressive environment that enables myeloma cells to avoid detection by the immune system and continue to survive even after treatment [ 146 ]. Furthermore, exosomes play a role in the survival of MDSCs by activating STAT3 and enhancing their immunosuppressive characteristics [ 147 , 148 ].…”
Section: Bone Marrow: a Specialty That Fosters Growthmentioning
confidence: 99%
“…Experiments have demonstrated that exosomes derived from BMSCs provide a safeguard against bortezomib by activating certain proteins (c-Jun, p38, p53, AKT) and influencing the expression of Bcl-2, caspase 9, caspase 3, and PARP [ 145 ]. In addition, exosomes have the ability to influence the immune response in the BMME, creating a suppressive environment that enables myeloma cells to avoid detection by the immune system and continue to survive even after treatment [ 146 ]. Furthermore, exosomes play a role in the survival of MDSCs by activating STAT3 and enhancing their immunosuppressive characteristics [ 147 , 148 ].…”
Section: Bone Marrow: a Specialty That Fosters Growthmentioning
confidence: 99%